Traditional Chinese Medicine nursing for a patient with chronic gastritis and constipation (1例慢性胃炎合并便秘患者的中医护理体会) - HOU Xuemin (侯雪敏); HUANG Yanping (黄砚萍); LI Mingzhu (李明珠) (Association of Integrative Nursing, 2023)
This paper summarized the Traditional Chinese Medicine (TCM) nursing for a patient with chronic gastritis and constipation. Based on the TCM syndrome differentiation, the Bian-stone ironing-massage and Chinese herbal medicine penetration were carried out to relieve the symptoms of constipation. The case management was adopted for regulating spleen-stomach and improving the recovery of gastrointestinal function. (本文总结1例慢性胃炎合并便秘患者的中医护理体会。通过辨证分型, 采取砭石熨摩中药透入法治疗技术, 为患者进行个案护理管理, 调理脾胃, 促进胃肠功能恢复。)